2012
DOI: 10.5005/jp-journals-10012-1077
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Gingival Phenotype, Residual Ridge Height and the Schneiderian Membrane

Abstract: Purpose: Sinus perforations are one of the most common complications during sinus augmentation procedures. Preoperative prediction of the antral membrane thickness would be of practical importance and serves as an additional information for surgical planning. The purpose of this study was to analyze a possible correlation and comparison between gingival phenotype and the residual ridge height on the dentulous and the edentulous side to the thickness of the healthy sinus mucosa.Materials and methods: Twenty-fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 79 publications
0
12
1
1
Order By: Relevance
“…36 37 Some authors reported that healthy Schneiderian membranes are thicker in individuals with a thick gingival biotype than in those with a thin gingival biotype. 11,38 However, our results showed no correlation between the membrane thickness and crestal gingival thickness.…”
Section: Discussioncontrasting
confidence: 55%
“…36 37 Some authors reported that healthy Schneiderian membranes are thicker in individuals with a thick gingival biotype than in those with a thin gingival biotype. 11,38 However, our results showed no correlation between the membrane thickness and crestal gingival thickness.…”
Section: Discussioncontrasting
confidence: 55%
“…As an additional and important result, the present authors were able to measure the gingival thickness, which is one of the predictors of the gingival phenotype. Its variation has direct implications on the results of periodontal therapy, root coverage procedures, implant placement, and surgeries for maxillary sinus elevation owing to the strong correlation between the gingival phenotype and the Schneiderian mucosa thickness 34,35 . Several methods have been used, both invasive and non‐invasive, to evaluate gingival thickness, such as histologic sections, injection needles, transgingival probing, cephalometric radiographs, probe transparency, ultrasonic devices, and cone beam computed tomography 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Its variation has direct implications on the results of periodontal therapy, root coverage procedures, implant placement, and surgeries for maxillary sinus elevation owing to the strong correlation between the gingival phenotype and the Schneiderian mucosa thickness. 34,35 Several methods have been used, both invasive and non-invasive, to evaluate gingival thickness, such as histologic sections, injection needles, transgingival probing, cephalometric radiographs, probe transparency, ultrasonic devices, and cone beam computed tomography. 36 Another way is visual evaluation, but that cannot be considered a reliable method to determine the degree of gingival thickness because of its qualitative nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study group showed statistically significant correlation between bone height and width, which means, the higher is the alveolar bone, the wider the bone is. It is found that in cases of lower residual bone, perforation of the Schneider membrane is observed more often (Deepthi, 2012), which is explainable by thinner bone and smaller cavities. In our study, no such links were found.…”
Section: Alveolar Bone and Maxillary Sinus Floor Augmentation Area Measurementsmentioning
confidence: 92%